Human Resource Limitations and Their Impact on Teacher Competence and Quality Assurance in Islamic Education in Indonesia - Sajidin Sajidin; Muaripin Muaripin; Ary Maulana Muaripin; Muhammad Rifqi Fathurrahman; Muhamad Hanif Al-Haya Muaripin (AR-RASYID : Jurnal Pendidikan Agama Islam, 2026)
Islamic education in Indonesia, particularly in institutions under the Ministry of Religious Affairs, continues to encounter challenges in maintaining educational quality. This study aims to examine the factors influencing teacher competence in madrasas and analyze their impact on educational quality. A qualitative case study approach was employed, with data collected through in-depth interviews involving teachers, school principals, and relevant government officials. The findings reveal that limited access to professional development programs, uneven policy implementation, and inadequate incentive systems are the primary factors contributing to low teacher competence. These constraints hinder the effectiveness of instructional practices and negatively affect student learning outcomes. Furthermore, disparities in resource distribution between regions exacerbate the issue, particularly in marginalized areas. In conclusion, improving teacher competence is essential to enhancing the quality of Islamic education. This study recommends expanding access to continuous professional development, ensuring equitable policy implementation, and strengthening incentive mechanisms for educators. These efforts are expected to support sustainable improvements in teaching quality and student achievement within madrasas in Indonesia.